Multi-Component BEM for the Helmholtz Equation: A Normal Derivative Method - H.A.M. Ben Hamdin; G. Tanner (Shock and Vibration)
We describe a multi-component boundary element method for predicting wave energy distributions in a complex built-up system with material properties changing discontinuously at boundaries between sub-components. We point out that depending on the boundary conditions and the number of interfaces between sub-components, it may be advantageous to use a normal derivative method to set up the integral kernels. We describe how the resulting hypersingular integral kernels can be regularised. The method can be used to minimise the number of weakly singular integrals thus leading to BEM formulations which are easier to handle.